Implementasi Sistem Informasi Penerimaan Siswa Baru - Sunarti - AMIK BSI Jakarta (Universitas Bina Sarana Informatika, 2015)
Abstract - New admissions process conducted by each school , both public and private , as also happened in SMP Islam Assalamah Cipayung . Problems that occur in the new admissions process that exist in Islam Assalamah Cipayung SMP is still used in manual form , resulting in long queues for prospective students and parents in the process of registration of new students . To solve these problems the authors build information systems in the new admissions process using software development with Waterfall . For a data model is described by the functional model and ERD (Entity Relationship Diagram). The method used is the analysis , data collection and implementation . With the website Admission of new students more effectively and efficiently based on the ease of obtaining student data , school promotion and communication between parents and the school Keywords : Implementation , information systems , Reception of students